The Efficacy Of Adding Muscle Energy Technique To A Participatory Ergonomic Approach To Reduce Pain And Improve Functional Ability In Employees With Mechanical Neck Pain In A Private Company In West Kalimantan - Yuliana, Yuliana; Purnawati, Susy; Muliarta, I Made (Sean Institute, 2024)
Employees of Credit Union Lantang Tipo (CULT) work in abnormal postures using computers causing mechanical neck pain (MNP) characterised by complaining of pain and reduced functional ability. This study aims to prove the efficacy of adding muscle energy technique (MET) to the participatory ergonomics approach (PEP) to reduce pain and improve functional ability in employees with MNP. This study used a true experimental design involving 40 subjects (n=20), consisting of treatment group I (PEP)) and treatment group II (addition of MET to PEP). Pain measurement used VAS and functional ability used NDI. Data analysis used Independent-Samples T-Test with a significance level of 5% (α = 0.05). The results of this study are that there is a significant difference in the mean after intervention, treatment group I (VAS 5 ± 0.59 p = 0.00, NDI 22.60 ± 6.77 p = 0.01) and treatment group II (VAS 3.5 ± 0.66 p = 0.00, NDI 17.80 ± 4.15 p = 0.01) with a p value <0.05. The decrease in the mean score of VAS and NDI in treatment II was greater than treatment I. The conclusion of this study is that the added MET to PEP is proven to be more effective in reducing pain and improving functional abilities in employees with MNP.